Is Russia Still Isolated? - Cheang, Chris (2018)
It has been widely written that Russia has been internationally isolated since the 2014 Crimean and Ukraine crises as well as a host of other critical events that triggered Western economic and political sanctions. However, this assertion can increasingly be called into question.